The Need Analysis of Music Department Students to Learn English by Using the Project-Based Approach with Song Lyrics Writing as Supporting Technique - Prima Dona Hapsari (Institut Seni Indonesia Yogyakarta, 2015)
The modern education system and strategies to achieve competitiveness, collaboration, and creativity are being the main focus of Indonesian higher education. They actively give positive influence to English teachers at Indonesia Institute of the Arts of Yogyakarta who particularly seek for the appropriate technique in transferring English to art students who need English as their potential engagement to the world of arts and life. For a project-based approach becomes a part of English for Special Purposes, it has been, therefore, one of the alternative approaches proposed to music students for which English is necessarily needed to accommodate their competence. The need analysis of music students would be essential to find out the appropriate techniques to teach English to art students. Therefore, the research was aimed to analyze the need analysis of music students who did the song lyrics writing as the project in English learning and to find out the significant result of implementing the project in the English class of art students of Music Department. The research used qualitative method which addressesed to descriptive analysis. The subject of this research was students of music department who were divided into six groups consisting of four to five students each, and were selectively chosen based on the purposive-sample method. The research result could be well accepted that music students produced English song lyrics and performed it as well